TEACHER PERFORMANCE EVALUATION SYSTEMS: CATALYSTS FOR PROFESSIONAL DEVELOPMENT AND SCHOOL IMPROVEMENT - Jusoh, Rosnani; Zhao , Shuo; Bakri, Eisya Eirika Mohd (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper examines teacher performance evaluation systems as strategic mechanisms for fostering professional development and advancing school improvement. In the context of global educational reform, teacher evaluation has evolved from a traditional supervisory tool into a developmental approach that enhances teacher growth and institutional effectiveness. Adopting a conceptual research method, the study systematically reviews domestic and international literature through the lens of educational management theories, motivation theories, and continuous professional development models. The review highlights the positive roles of evaluation in improving teaching quality, motivating teachers, and informing education policy. Findings suggest that a scientific and well-designed evaluation system can optimize teacher resource allocation, strengthen professional awareness, and raise the overall management capacity of schools. To enrich the analysis, three classical performance management theories—Management by Objectives (MBO), Expectancy Theory (Vroom), and Equity Theory (Adams)—are introduced to demonstrate their practical value in shaping teacher evaluation practices. Furthermore, the paper compares widely used evaluation methods in education, including Key Performance Indicators (KPIs), 360-degree feedback, Behaviorally Anchored Rating Scales (BARS), and MBO. Through the analysis of real-world cases, the study identifies persistent challenges, such as poorly designed indicators, weak alignment between evaluation and incentives, lack of fairness, and insufficient feedback mechanisms. In response, it proposes optimization strategies that include differentiated goal setting, effective incentive structures, enhanced transparency, and improved feedback and data utilization. These strategies aim to better support teacher professional development and improve the overall quality of education. ,